PENGEMBANGAN BULETIN MARI BELAJAR IPA (MALAPA) PADA PEMBELAJARAN IPA DI MTs NEGERI 2 JEMBER - Ratna Sari; Rif'ati Dina Handayani; Pramudya Dwi Aristya Putra (JURNAL PEMBELAJARAN FISIKA, 2017)
MALAPA bulletin is a supplemental teaching material that is attractively presented to give new nuance in teaching and learning process and to make the students able to understand the materials at ease. This research is meant to create a new product; MALAPA bulletin, that is appropriate to be used in teaching and learning process. The purposes of this research are: to produce a valid bulletin, to describe student’s interests and to know student’s thinking abilities toward the usage of Mari Belajar IPA (MALAPA) bulletin. The development design implemented in this research was 4-D development model. The results of the research show that the bulletin is valid category with 4.11 of expert validity. Student’s interest percentage toward the teaching and learning uses MALAPA bulletin is 83.54% with a good category. Student’s critical thinking ability percentage acquired 78.5% with a good category. MALAPA bulletin developed is weekly published where it contains materials that is modified as attractive as possible like warta sains, komik strip, TTSains, pantun sains, as well as the exercises. Based on this research result, it can be concluded that MALAPA bulletin is appropriate to be used as an interesting supplemental teaching material.